MEMBANGUN PEMAHAMAN MASYARAKAT KABUPATEN SAMBAS TERHADAP TAREKAT AL-MU’MIN MELALUI LITERASI INFORMASI - Rendi Purnama (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2021)
This study aims to build the understanding of the people of Sambas Regency towards the Al-Mu'min Order through information literacy. Using a qualitative descriptive method with a case study approach. The results of this study indicate that in order to build community literacy towards the Al-Mu'min Order, members of the Al-Mu'min Order try to carry out literacy in the community through writings that are directly related to the Al-Mu'min Order. The writings that become the basis for building public understanding of the Al-Mu'min Order are books that have been published including a book entitled “Rahasia Perjalanan Menuju Allah, Khazanah Al-Mu’min Mutiara Ilmu Konsep dan Ajaran Thariqah Al Mu’min dan Perguruan Benteng Mu’min”, and the last is a book entitled “Hakikat Tarekat Al-Mu’min”. In addition, the Al-Mu'min Tarekat assembly also established the Assatidz Assembly as a means of proof and a means of getting to know the Al-Mu'min Order to the public. One of the activities carried out by the Assatid Council of the Al-Mu'min Order in building public literacy regarding the Al-Mu'min Order is to conduct Friday safaris at mosques in Sambas Regency.